Electronic transfer taxes and the stock market: empirical evidence from Ghana’s E-levy - John Boamah; Ernestina Ohenewaah Denchie; Aurelia Naa Ayikaikor Ayi-Bonte (Cogent Economics & Finance)
This paper aims to highlight the correlation between Ghana’s Electronic Transfer Levy (E-levy) and the stock market performance of the target firms. Initially, the E-levy aimed to raise GH₵7 billion by taxing electronic transfers exceeding GH₵100 daily at a rate of 1.75%. Following a rate reduction to 1.5%, the revenue target was revised to GH₵4.5 billion. Using a difference-in-differences approach, we find a negative effect on target firm stock prices, persisting around the implementation period. We also find that reducing the levy influences stock prices positively. Our channel test reveals that the levy affects the stock market through transaction volume, with a stronger result for firms with below-average trading volumes. The policy recommendation is to reduce the rate below 0.5%.